"Well, it's nobody's responsibility but my own." A qualitative study to explore views about the determinants of health and prevention of knee pain in older adults - Jinks, Clare (BioMed Central, 2010)
BACKGROUND: Dahlgren and Whitehead's 'rainbow' outlines key determinants of health and has been widely adopted within public health policy and research. Public understanding regarding the determinants of health is, however, relatively unknown, particularly in relation to common chronic joint problems like knee pain. We aimed to explore individual attitudes to the prevention of knee pain, and assess how people make sense of their lives by using the rainbow model to explore social determinants of health. METHODS: Twenty-eight semi-structured interviews were undertaken with older adults living in the community. The format of the interview enabled individuals to first tell their story, then the rainbow picture was used to further prompt discussion. Interviews were digitally recorded and transcripts were fully transcribed. Qualitative computer software package NVivo 2 was used to manage the data. Thematic analysis was undertaken. RESULTS: Individual responsibility for health was a dominant theme although the role of health and statutory services was also recognised. Barriers to uptake of prevention activities included cultural perceptions, attitudes towards work and perceived costs of prevention activities. Participants used the rainbow for locating their personal life within a wider social, economic and policy context. CONCLUSIONS: People view individual responsibility as key to maintaining health and draw upon the past, present and future expectations when considering social determinants of their health. The rainbow picture does have relevance at the individual level and can help to formulate more dynamic and contextualised approaches to the prevention of health conditions in community living adults.